Consumption Network Effects - Giacomo De Giorgi; Anders Frederiksen; Luigi Pistaferri (Institute for the Study of Labor (IZA), 2016)
In this paper we study the relevance and mechanics of consumption network effects. We use long panel data on the entire Danish population to construct a measure of consumption based on administrative tax records, and define the peer groups in terms of workplace, occupation, education, and age. We then apply an IV strategy, and fixed effect models, to recover the effects. Our instruments arise naturally from the network structure and firms shocks. The estimated effects are statistically significant and relevant for policies as they generate non-negligible multiplier effects. Further, the results are consistent with a "Keeping-up" model.
Keywords: E21; D12; D85; 330; consumption; networks; social multiplier; risk sharing